Role of duodenal mucosal nerve endings in the acid‐induced duodenogastric sensorimotor reflex: Effect of benzocaine in healthy humans. Issue 5 (9th April 2013) - Vanuytsel, T.; Karamanolis, G.; Vos, R.; Van, L.; Farré, R.; Tack, J.
Abstract Background Duodenal acid exposure induces a duodenogastric reflex resulting in gastric relaxation, inhibition of antral motility, and sensitization of the proximal stomach to distension. Duodenal hypersensitivity to acid has been identified as a potential pathogenic mechanism in functional dyspepsia. The nature and localization of the duodenal acid‐sensitive receptors are still elusive. We hypothesize that acid directly activates superficial afferent nerve endings in the duodenal mucosa, triggering the duodenogastric reflex. Methods In a double‐blind, randomized, crossover study in 13 healthy volunteers, benzocaine, a local anesthetic, vs saline was perfused in the duodenum 15 min before duodenal acid perfusion. Gastric responses were monitored by a barostat. Stepwise isobaric gastric distensions were performed before and during acid perfusion. Symptoms were evaluated by visual analogue scales for six dyspeptic symptoms and an overall perception score. Key Results Benzocaine perfusion caused a relaxation of the stomach prior to duodenal acidification, indicating the existence of an excitatory duodenogastric tone. Pretreatment of the duodenum with benzocaine reduced the acid‐induced gastric relaxation by 50% and abolished the inhibition of phasic motility of the proximal stomach. Finally, sensitization to distension was more pronounced in the benzocaine condition because of higher proximal gastric volumes. Conclusions & Inferences These findings support a model in which different neuronal subpopulations are responsible for the motor and sensory limb of the acid‐sensitive duodenogastric reflex, making benzocaine an unsuitable drug to treat duodenal hypersensitivity to acid. These data provide more insight in the contribution of duodenal neuronal input to gastric physiology in the fasting state.